Spirit of hope - Graham, Bob (Greenvale, New York : Mondo Publishing, 1996)
When the Fairweather family almost gives up hope of findinf a place to live, the youngest child gives them idea for a great location.
Keywords: Hope-Fiction; Moving, Household-Fiction; Family life-Fiction